The Value of Pancasila on the Islamic Education Institution (Discourse Study of the Al-Imamah Book at SMA Al-Islam 1 Surakarta) - Galih Pranata (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2021)
Pancasila has become the ideology of the Indonesian nation, including the Islamic Foundation which is often juxtaposed with a non-Pancasila stigma that demands a caliphate state and abandons the values of Pancasila. Islamic foundations have always been a sentiment in Indonesian society today, so it is necessary to further ascertain the teachings conveyed by the Islamic Foundation, more specifically from the perspective of education. This study aims to see the existence of Pancasila in the social interactions of the Islamic Education Foundation, especially in SMA Al-Islam 1 Surakarta. The method in this study uses a qualitative paradigm through an interview approach and participatory observation. The results of this study indicate that there is a special study for teachers and employees at SMA Al-Islam 1 Surakarta using the book Al-Imamah by Kiyai Haji Imam Ghazali. This book is a summary of K. H Imam Ghazali's intellectual activities in the journey and history of struggle to build Al-Islam college as outlined through his writings and analysis of the holy verses of the Koran and Hadith as the founding principles of the Al-Islam Foundation itself. There is an implicit emphasis on the values of Pancasila contained in the book of Al-Imamah and it is conveyed periodically with a frequency of once a week. This study is expected to provide provisions and instill the values of religiosity and personality in acting and behaving.